DEMENTIA AND THE LOADED GUN: KEEPING AND BEARING ARMS WHEN COGNITION AND CAPACITY BECOME COMPROMISED. (11th November 2018) - Graham, A; Langston, A; Griffiths, P
Abstract: The physical environment is fraught with potential dangers that can jeopardize the safety of a person living with dementia and his or her family carepartner. For rural Veterans, one common source of danger is the presence of firearms in the home environment. A loaded gun in the house becomes particularly problematic as dementia progresses and cognition and capacity become compromised. However, the second amendment guarantees United States Citizens the right to keep and bear arms. In this paper we present preliminary data on a sample of 18 rural Veterans and their carepartners who participated in a tele-dementia assessment as part of the national GRECC Connect program. All but one Veteran (94%) had a diagnosis of dementia and was accompanied by a family caregiver (89% spouses). The dyads underwent an in-person psychosocial interview battery administered by the team research psychologist followed by a comprehensive clinical assessment conducted with the clinic geriatrician via tele-video-conferencing. Fifty-three percent of the Veterans seen were over 80 years of age. Sixty-seven percent scored 10 or below on the St Louis University Mental Status (SLUMS) examination indicating impaired cognition and suggestive of reduced capacity. Seventy-eight percent of the sample carry a loaded gun and 83% keep one in the home and/or vehicle. Qualitative comments from the caregivers include fear and discomfort with the firearms in the home. A case study is presented to illustrate the challenges encountered with providers, family members and law enforcement. Results are discussed in terms of clinical, practical and policy implications.